2005
DOI: 10.1002/ppul.20157
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic efficacy of milrinone in the management of enterovirus 71‐induced pulmonary edema

Abstract: Hand, foot, and mouth disease and herpangina are the major clinical manifestations of enterovirus 71 (EV71) infections. Brain-stem encephalitis and pulmonary edema are severe complications that can lead to death. This study was designed to evaluate the potential therapeutic effect of milrinone, a phosphodiesterase (PDE) inhibitor, in the treatment of patients with EV71-induced pulmonary edema. We conducted a historically controlled trial of 24 children with severe EV71-induced pulmonary edema from April 1998-J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
50
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 27 publications
2
50
2
Order By: Relevance
“…In a smaller proportion of patients (32, 21.8%), amrinone, a cyclic nucleotide phosphodiesterase inhibitor, was used in the treatment of congestive heart failure. Although the effect of amrinone in treating heart failure following HFMD has not been prospectively studied, a retrospective analysis of a similar drug, milrinone, showed that in children with EV71-induced pulmonary edema milrinone treatment was associated with a reduced tachycardia and lower mortality [18]. …”
Section: Discussionmentioning
confidence: 99%
“…In a smaller proportion of patients (32, 21.8%), amrinone, a cyclic nucleotide phosphodiesterase inhibitor, was used in the treatment of congestive heart failure. Although the effect of amrinone in treating heart failure following HFMD has not been prospectively studied, a retrospective analysis of a similar drug, milrinone, showed that in children with EV71-induced pulmonary edema milrinone treatment was associated with a reduced tachycardia and lower mortality [18]. …”
Section: Discussionmentioning
confidence: 99%
“…Overproduction of specific inflammatory cytokines, interleukin (IL)-10, IL-13, and interferon (IFN)-␥ is strongly associated with PE [8]. Administration of milrinone, a phosphodiesterase inhibitor, and intravenous immunoglobulin has been shown to decrease sympathetic overactivity, decrease inflammation, and improve survival in patients with EV71-associated PE [10,11]. Controlled clinical trials are needed to confirm this observation.…”
mentioning
confidence: 90%
“…Peripheral white cell and platelet counts and plasma IL-13 concentrations were also lower, which might indicate an immunomodulatory effect of the drug. 53,54 Use of large volumes for management of shock with EV 71 outbreaks in Asia, frequently precipitated PE. After it became clear that impaired cardiac function is an important contributor to shock, clinicians were more judicious in their use of intravenous fluids and used inotrope support.…”
Section: Supportive Therapymentioning
confidence: 99%